Future NATO : adapting to new realities - Olsen, John Andreas, 1968-; Royal United Services Institute for Defence and Security Studies (Abingdon : Routledge Journals, 2020)
"Future NATO completes a trilogy of security and defence publications in RUSI's Whitehall Paper series. The first - NATO and the North Atlantic: Revitalising Collective Defence (2017) - focuses on the renewed importance of the transatlantic bond from US, UK and Norwegian perspectives. The second - Security in Northern Europe: Deterrence, Defence and Dialogue (2018) - takes a broader view, analysing challenges confronting the 12 Northern Group countries, the US and Canada. Both papers were publicised through comprehensive outreach programmes and presented at seminars in 25 countries, with the objective of encouraging an informed and open debate on national policy and international relations with emphasis on the northern region. That debate served as an input for this third Whitehall Paper."
"Future NATO: Adapting to New Realities (2020) expands the view further, identifying key themes that the Alliance and its partners must examine and address to remain relevant in the decades to come. As NATO recently celebrated 70 years of 'credible deterrence and collective defence', this paper focuses on what NATO members should do, individually and together, to strengthen the organisation in order to meet present and future challenges."--Preface.
Foreword / Tod D. Wolters -- Introduction : An alliance for the 21st century / John Andreas Olsen -- NATO's enduring relevance / Svein Efjestad and Rolf Tamnes -- Permanent deterrence and the US military presence in Europe / Alexander R. Vershbow and Philip M. Breedlove -- NATO as a partner / Malcolm Chalmers -- The evolution of the Russian threat to NATO / Andrea Kendall-Taylor and Jeffrey Edmonds -- NATO's China challenge / Janka Oertel -- NATO and its southern flank / Ziya Meral -- NATO's maritime domain / Keith Blount and James Henry Bergeron -- Maintaining NATO's technological edge / Tim Sweijs and Frans Osinga -- NATO's nuclear posture and arms control / Corentin Brustlein -- The need for the alliance to adapt further / Heinrich Brauss.
"Published on behalf of the Royal United Services Institute for Defence and Security Studies"--Title page verso.
OCLC-licensed vendor bibliographic record.
Keywords: North Atlantic Treaty Organization -- Armed Forces; National security -- International cooperation; Europe -- Defenses -- Strategic aspects; United States -- Defenses -- Strategic aspects; POLITICAL SCIENCE / International Relations / General